Why Do Patients With Ischaemic Heart Disease Drop Out From Cardiac Rehabilitation in Primary Health Settings. A Qualitative Audit of Patient Charts - Ravn, Maiken Bay; Uhd, Maria; Svendsen, Marie Louise; Ørtenblad, Lisbeth; Maribo, Thomas (Frontiers in Rehabilitation Sciences, 2022)
Background Cardiac rehabilitation (CR) and medical treatment are integrated parts of the intervention for cardiac patients and are a class 1A recommendation. However, CR dropout is reported to be relatively high and little is known about the reasons for CR dropout in primary health settings. Aim This study investigates causes for CR dropout through a qualitative audit of medical charts among patients with ischaemic heart disease. Methods This was a qualitative retrospective audit of patients' medical charts. Patients who dropped out from CR between 1 January to 31 December 2018 in five primary health settings were included. Local patient charts provided information related to causes and formed the basis of the analysis. Data were analysed using thematic analysis. Results A total of 690 patients were referred for and commenced CR and 199 (29%) dropped out. Twenty-five (12.6%) patients finished CR but were excluded due to standards of ≥ 180 days between CR meetings, leaving 118 patients included. Four themes as causes for patients' dropout were identified: (1) CR-programmes, (2) logistical, (3) intrapersonal and (4) clinical factors. Conclusion This study identified new focus areas to which health professionals may attend in reducing drop-out from CR. Organisation of CR, challenges with combining labour market attachment and CR, focus on patient education and comorbidities. The results underline the importance of health professionals emphasizing the benefits of CR and explains that CR enhances long-term labour market attachment. Furthermore, health professionals should encourage participation in patient education and adapt exercise to the individual patient’s potential.